Respuesta :

Answer:  see proof below

Step-by-step explanation:

Use the following Half-Angle Identities:    tan (A/2) = (sinA)/(1 + cosA)

                                                                     cot (A/2) = (sinA)/(1 - cosA)

Use the Pythagorean Identity: cos²A + sin²B = 1

Use Unit Circle to evaluate: cos 45° = sin 45° = [tex]\frac{\sqrt2}{2}[/tex]

Proof LHS → RHS

Given:                       [tex]cot\ (22\frac{1}{2})^o-tan\ (22\frac{1}{2})^o[/tex]

Rewrite Fraction:     [tex]cot\ (\frac{45}{2})^o-tan\ (\frac{45}{2})^o[/tex]

Half-Angle Identity:   [tex]\dfrac{sin(45)^o}{1-cos(45)^o}-\dfrac{sin(45)^o}{1+cos(45)^o}[/tex]

Substitute:                  [tex]\dfrac{\frac{\sqrt2}{2}}{1-\frac{\sqrt2}{2}}-\dfrac{\frac{\sqrt2}{2}}{1+\frac{\sqrt2}{2}}[/tex]

Simplify:                      [tex]\dfrac{\frac{\sqrt2}{2}}{\frac{2-\sqrt2}{2}}-\dfrac{\frac{\sqrt2}{2}}{\frac{2+\sqrt2}{2}}[/tex]

                               [tex]=\dfrac{\sqrt2}{2-\sqrt2}-\dfrac{\sqrt2}{2+\sqrt2}[/tex]

                               [tex]=\dfrac{\sqrt2}{2-\sqrt2}\bigg(\dfrac{2+\sqrt2}{2+\sqrt2}\bigg)-\dfrac{\sqrt2}{2+\sqrt2}\bigg(\dfrac{2-\sqrt2}{2-\sqrt2}\bigg)[/tex]

                               [tex]=\dfrac{2\sqrt2+2}{4-2}-\dfrac{2\sqrt2-2}{4-2}[/tex]

                               [tex]=\dfrac{4}{2}[/tex]

                               = 2

LHS = RHS:  2 = 2  [tex]\checkmark[/tex]

Ver imagen tramserran
Ver imagen tramserran